CDK6 is essential for mesenchymal stem cell proliferation and adipocyte differentiation - Hu, Alexander J.; Li, Wei; Pathak, Apana; Hu, Guo-Fu; Hou, Xiaoli; Farmer, Stephen R.; Hu, Miaofen G. (Frontiers in Molecular Biosciences, 2023)
Background: Overweight or obesity poses a significant risk of many obesity-related metabolic diseases. Among all the potential new therapies, stem cell-based treatments hold great promise for treating many obesity-related metabolic diseases. However, the mechanisms regulating adipocyte stem cells/progenitors (precursors) are unknown. The aim of this study is to investigate if CDK6 is required for mesenchymal stem cell proliferation and adipocyte differentiation. Methods: Cyclin-dependent kinase 6 (Cdk6) mouse models together with stem cells derived from stromal vascular fraction (SVF) or mouse embryonic fibroblasts (MEFs) of Cdk6 mutant mice were used to determine if CDK6 is required for mesenchymal stem cell proliferation and adipocyte differentiation. Results: We found that mice with a kinase inactive CDK6 mutants (K43M) had fewer precursor residents in the SVF of adult white adipose tissue (WAT). Stem cells from the SVF or MEFs of K43M mice had defects in proliferation and differentiation into the functional fat cells. In contrast, mice with a constitutively active kinase CDK6 mutant (R31C) had the opposite traits. Ablation of RUNX1 in both mature and precursor K43M cells, reversed the phenotypes. Conclusion: These results represent a novel role of CDK6 in regulating precursor numbers, proliferation, and differentiation, suggesting a potential pharmacological intervention for using CDK6 inhibitors in the treatment of obesity-related metabolic diseases.